Upekkhadhamma in Theravada Buddhist Philosophy towards the Importance of Life Development - Krongboon, Phornsawan (Journal of Dhamma for Life, 2022)
This academic article aims to study Upekkhadhamma in Theravada Buddhist Philosophy towards the Importance of Life Development. Neutral trust that is not inclined to likes or dislikes and is not intolerant. The use of discernment to consider results that are reasonable to a cause and to continue to act according to that cause, without happiness or suffering, is called “Upekkha Bhavana”. In general, equanimity means passivity. Or having a consistent mind, equalizing the state of mind, having the knowledge and ability to keep up with the emotions that are good and bad with wisdom. The control of one's mind not to be moved by that particular emotion is important to the equanimity because it maintains a neutral state and has a normal state of discontent and no regret in form sounds, smells, tastes, touches and dharmas that have been experienced. That person would not feel suffering or happiness. Considering that all beings are subject to the power of karma, they are able to maintain their neutrality even though they have a mind full of compassion and compassion. Will help in the force majeure of the karma that determines. Reaching neutrality without suffering is an unshakable state of mind. Being determined and not being influenced by defilement is an essential characteristic of equanimity and a profound doctrine necessary for human coexistence. Which makes the society peaceful with the ultimate goal of liberation from the cycle of suffering.